1994
DOI: 10.1007/bf00206236
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of color opponent representation by a three-layered neural network model

Abstract: This paper discusses color representation in the visual system by analysis of a three-layered neural network model. The model incorporates physiological knowledge of color representation at the sensor level (broad-band trichromatic representation by cones) and the higher level (narrow-band color representation by color-coded cells in V4). We trained the model to perform a mapping between these color representations by the back propagation algorithm and analyzed the acquired characteristics of the hidden units.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For instance, the red-green channel is very sensitive to complementarycolour pairs that include red and green. Experimental evidence suggests that the opponent channels arise naturally in artificial neural networks (Usui et al, 1994) or as the independent components of natural images (Lee et al, 2002;. Biological studies have revealed that individual neurons in the visual system respond to opponent-colours (De Valois and De Valois, 2000).…”
Section: Opponent Channelsmentioning
confidence: 99%
“…For instance, the red-green channel is very sensitive to complementarycolour pairs that include red and green. Experimental evidence suggests that the opponent channels arise naturally in artificial neural networks (Usui et al, 1994) or as the independent components of natural images (Lee et al, 2002;. Biological studies have revealed that individual neurons in the visual system respond to opponent-colours (De Valois and De Valois, 2000).…”
Section: Opponent Channelsmentioning
confidence: 99%
“…Buchsbaum and Gottschalk [Buchsbaum 1983] have shown that efficient information transmission is achieved by opponent color coding. Usui et al [Usui 1991[Usui , 1994 trained neural network models by means of a backpropagation algorithm. The hidden units learned characteristics similar to those of opponent color cells known from neurobiology.…”
Section: Introductionmentioning
confidence: 99%